2021
DOI: 10.1159/000517222
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Mycotic Aneurysm: Superior Mesenteric Artery Aneurysm Caused by <b><i>K. pneumoniae</i></b>

Abstract: We herein report a rare case of mycotic aneurysm of the superior mesenteric artery caused by <i>Klebsiella pneumoniae</i>. A 66-year-old man, a known case of hypertension and aorto-oesophageal fistula with stented aorta in 2010 and 2018, presented to the emergency department multiple times over 2 months with severe postprandial abdominal pain associated with vomiting and fever. On his last presentation, the obtained blood cultures grew ESBL positive <i>K. pneumoniae</i> and a repeated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several studies have reported successful visceral mycotic aneurysm treatment via aneurysmectomy with vessel stump closure without vascular reconstruction (primary aneurysmectomy). 9 , 10 However, aneurysmectomy alone for mesenteric aneurysms is associated with bowel resection in 10% of cases, 14 which poses additional postoperative risks such as anastomotic leakage and stricture. Revascularization should be considered if the affected branches supply a significant portion of bowel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported successful visceral mycotic aneurysm treatment via aneurysmectomy with vessel stump closure without vascular reconstruction (primary aneurysmectomy). 9 , 10 However, aneurysmectomy alone for mesenteric aneurysms is associated with bowel resection in 10% of cases, 14 which poses additional postoperative risks such as anastomotic leakage and stricture. Revascularization should be considered if the affected branches supply a significant portion of bowel.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The risk of progression to sepsis and rupture is high if not treated with antibiotics and, in most cases, surgery. Previous case reports have described treatment success with both open aneurysm resection without vascular reconstruction 9 , 10 and endovascular repair. 8 , 11 …”
mentioning
confidence: 99%